Taurine Regulates Mitochondrial Function During 7,12-Dimethyl Benz[a]anthracene Induced Experimental Mammary Carcinogenesis - Manickam Kalappan Vanitha; Kalpana Deepa Priya; Kuppusamy Baskaran; Kuppusamy Periyasamy; Dhravidamani Saravanan; Ramachandran Venkateswari; Balasundaram Revathi Mani; Aruldass Ilakkia; Sundaramoorthy Selvaraj; Rajendran Menaka; Mahendran Geetha; Nadarajah Rashanthy; et al. (Korean Pharmacopuncture Institute, 2015)
Objectives: The present study was undertaken to determine the modulatory effect of taurine on the liver mitochondrial enzyme system with reference to mitochondrial lipid peroxidation (LPO), antioxidants, major tricarboxylic acid cycle enzymes, and electron transport chain enzymes during 7,12-dimethyl benz[a]anthracene (DMBA) induced breast cancer in Sprague-Dawley rats. Methods: Animals in which breast cancer had been induced by using DMBA (25 mg/kg body weight) showed an increase in mitochondrial LPO together with decreases in enzymic antioxidants (superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione reductase (GR) and glutathione-S-transferase (GST)), non-enzymic antioxidants (reduced glutathione (GSH), vitamin C, and vitamin E), in citric acid cycle enzymes (isocitrate dehydrogenase (ICDH), alpha ketoglutarate dehydrogenase (alpha KDH), succinate dehydrogenase (SDH) and malate dehydrogenase (MDH)), and in electron transport chain (ETC) complexes. Results: Taurine (100 mg/kg body weight) treatment decreased liver mitochondrial LPO and augmented the activities/levels of enzymic, and non-enzymic antioxidants, tricarboxylic acid cycle enzymes and ETC complexes. Conclusion: The results of our present study demonstrated the chemotherapeutic efficacy of taurine treatment for DMBA-induced breast carcinomas.